Detection of low density lipoprotein receptor gene mutations in patients with familial hypercholesterolaemia / Rafezah Razali - Rafezah, Razali (2011)
Familial hypercholesterolaemia (FH) is an autosomal dominant inherited disorder of lipoprotein metabolism associated with premature coronary artery disease (CAD). Extrapolating the prevalence of heterozygous FH in western populations into Malaysian population, it would be estimated that about 50,000 Malaysians would be affected and at risk of developing premature CAD. Mutations of the low density lipoprotein receptor (LDLR) gene are the most frequent cause of FH but its genetic profiles in the Asian population has been poorly characterised. Therefore, in this study, the screening and characterisation of the LDLR gene mutations and its polymorphisms among patients with clinical diagnosis of FH were compared to normocholesterolaemic controls. Cross sectional study involving 74 FH patients (50 Malays & 24 Chinese) and 77 age-matched normocholesterolaemic controls were recruited. Diagnosis of FH was based on Simon Broome Register criteria. Blood samples were collected, serum and plasma were separated, stored and analysed for fasting serum lipids, glucose, renal profile, liver function tests and thyroid function test by standard automated laboratory techniques. Whole blood in EDTA tubes were collected and stored in -80 0C until DNA extractions were performed using a commercial kit. Genomic DNA purity was determined using a spectrophotometer. Gene amplification by polymerase chain reaction (PCR) was employed to amplify all exons (exon 1 – 18) and the promoter region of the LDLR gene. Mutation screening analysis was performed by denaturing high performance liquid chromatography (DHPLC). Samples showing heteroduplexes profiles by DHPLC were sequenced to confirm the location and nature of mutations using Sanger sequencing method. The present study detected five LDLR variants among 46 (62.2%) of FH patients in intron 3, exon 5, 9, 10 and 12 using DHPLC. Three different types of LDLR mutations were confirmed by Sanger sequencing in 6 out of 46 (13%) clinically-diagnosed FH patients. The identified mutations were in intron 3 (g.313+1G>A) of a FH patient of Chinese ethnicity, exon 5 (g.763T>A; C234S) of four FH patients of a Malay family and exon 9 (g.1216C>T; R385W) of a FH patient of Chinese ethnicity. Of the identified Malay family members, a homozygote and three heterozygotes for LDLR C234S mutation were found. Other variants identified were in exons 10 (g.1413G>A) and 12 (g.1773T>C). However, both variants in exons 10 and 12 did not cause amino acid change (arginine (R) at codon 450[AGG>AGA] and proline (N) at codon 570 [AAT>AAC]) respectively. In conclusion,the present work of employing molecular screening using DHPLC has been successfully optimised to detect the LDLR gene mutations. Combined with the clinicaldiagnosis criteria, the use of DNA-based screening method plays an important role in the definitive diagnosis of FH.